Social Grants as a Lifeline: Assessing Their Impact on Poverty Reduction in African Countries - Collin, Chikwira; Jahed, Mohammed Iqbal (International Journal of Economics and Financial Issues, 2025)
The study aims to evaluate the effectiveness of social grants in reducing poverty across ten African countries: South Africa, Kenya, Nigeria, Ghana, Tanzania, Uganda, Rwanda, Botswana, Namibia, and Ethiopia. It seeks to understand how these programs influence household income, poverty rates, and access to essential services within inclusive development. The study employs a Difference-in-Differences (DiD) approach and a Fixed Effects (FE) regression model to assess the impact of social grants from 2019 to 2023. The analysis is grounded in Keynesian economics and Amartya Sen’s capabilities approach, providing economic and human development perspectives. Findings indicate that social grants contribute to measurable improvements in household income, poverty reduction, and service access. The results further stressed that key constraints were identified as poor targeting, fiscal limitations, and potential long-term dependency. Social grants are effective tools for poverty alleviation, and their design and implementation require refinement to enhance sustainability and impact. The study provides robust empirical evidence and practical recommendations to policymakers and stakeholders. It supports expanding and optimising social grants as part of broader strategies for economic resilience, social inclusion, and equitable growth across Africa.